A new LaCo0.71(1)V0.29(1)O2.97(3) perovskite containing vanadium in octahedral sites: synthesis and structural and magnetic characterization1. Issue 23 (21st June 2015) - Fuertes, V. C.; Blanco, M. C.; Franco, D. G.; Ceppi, S.; Sánchez, R. D.; Fernández-Díaz, M. T.; Tirao, G.; Carbonio, R. E.
<x xml:space="preserve">Abstract</x> Powder neutron diffraction, Co-Kβ XES spectra and a polyhedral view of the orthorhombic LaCo0.71(1)V0.29(1)O2.97(3) perovskite.